2018
DOI: 10.1038/s41419-018-0724-5
|View full text |Cite
|
Sign up to set email alerts
|

Linc00462 promotes pancreatic cancer invasiveness through the miR-665/TGFBR1-TGFBR2/SMAD2/3 pathway

Abstract: Emerging evidence has identified that long non-coding RNAs (lncRNAs) may play an important role in the pathogenesis of many cancers, pancreatic cancer (PC) included. However, the role of linc00462 in PC remains unclear. The aim of our present study was to investigate the potential functions of linc00462 in PC and to identify the underlying mechanisms of action. CCK8 assay, transwell assay, cell cycle assay, cell apoptosis assay, EdU assay, western blot assay, cell adhesion assay, HE staining, IF staining, ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 42 publications
0
75
1
Order By: Relevance
“…18 A recent study reported that linc00462 may function as an effective invasiveness marker for pancreatic cancer patients, and linc00462 upregulation may promote pancreatic cancer cell invasiveness through the miR-665/TGFBR1-TGFBR2/Smad2/3 pathway. 19 In our study, we first found that NUSAP1 expression was positively correlated with the TGFBR1 and Smad2/3 pathways, as shown by GSEA. Furthermore, NUSAP1 expression was positively correlated with TGFBR1 expression, as shown by real-time PCR.…”
Section: Discussionmentioning
confidence: 55%
“…18 A recent study reported that linc00462 may function as an effective invasiveness marker for pancreatic cancer patients, and linc00462 upregulation may promote pancreatic cancer cell invasiveness through the miR-665/TGFBR1-TGFBR2/Smad2/3 pathway. 19 In our study, we first found that NUSAP1 expression was positively correlated with the TGFBR1 and Smad2/3 pathways, as shown by GSEA. Furthermore, NUSAP1 expression was positively correlated with TGFBR1 expression, as shown by real-time PCR.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, a previous study showed that PART1 can promote prostate cell proliferation and apoptosis by inhibiting TLR pathway activation (Sun, Geng, Li, Chen, & Zhao, 2018). LINC00462 is another confirmed oncogene that can enhance the progression of HCC and pancreatic cancer (Gong et al, 2017;Zhou, Guo, Sun, Zhang, & Zheng, 2018). CLLU1 mainly acts as a stable and inherent diagnostic biomarker of chronic lymphocytic leukemia and is significantly associated with poor clinical outcomes (Buhl et al, 2009;Gonzalez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA‐665 was downregulated in ovarian cancer, pancreatic cancer, hepatocellular carcinoma, inflammatory bowel disease, and so on. However, the role and mechanism of miR‐665 in CC remains unknown.…”
Section: Discussionmentioning
confidence: 99%